2021
DOI: 10.1038/s41387-021-00160-5
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin increases the lean-to total mass ratio in type 2 diabetes mellitus

Abstract: We compared the effect of dapagliflozin versus glibenclamide on the ratio of lean-to total mass in patients with type 2 diabetes mellitus, carotid subclinical atherosclerosis, HbA1c 7.0–9.0% and 40–70 years-old. Ninety-eight patients (61% male; mean age 57 ± 7 years) were randomized into dapagliflozin 10 mg/day or glibenclamide 5 mg/day on top of metformin. Body composition was measured by Dual Energy X-Ray at randomization and after 12 weeks of treatment. Glycemic control was equivalent in both groups. Dapagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The characteristics of the 18 included studies published between 2013 and 2022 are shown in Table 1 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The articles involved 1430 participants (726 SGLT-2 inhibitors participants…”
Section: Basic Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The characteristics of the 18 included studies published between 2013 and 2022 are shown in Table 1 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The articles involved 1430 participants (726 SGLT-2 inhibitors participants…”
Section: Basic Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Acknowledgements The authors would like to thank the participants, their families and all investigators involved in the VERTIS CV study; the list of investigators can be found with the primary publication [11]. Medical writing and/or editorial assistance was provided by M. Hammad and I. Norton, both of Scion (London, UK).…”
mentioning
confidence: 99%
“…Beyond this chronological dissociation, existing data have not shown a consistent change in muscle mass in response to SGLT2 inhibition in either direction. In fact, in four [ 4 – 7 ] of the six trials [ 4 9 ] with dapagliflozin (which is pharmacologically similar to ertugliflozin) quoted by the authors, there was no effect on measures of lean mass [ 10 ], whilst a recent active comparator (glibenclamide) trial showed an increase in lean:total body mass ratio with dapagliflozin use [ 11 ]. In addition to the inconsistent directional effects on measures of lean body mass, we also wish to emphasise that, even if changes in lean body mass did occur, this variable is composed of several factors, including muscle and water content.…”
mentioning
confidence: 99%
“…40 In a study performed to evaluate the effect of dapagliflozin versus glibenclamide on the ratio of lean-to-total mass in patients with T2D, it was found that dapagliflozin reduced total body mass but increased the ratio of lean-to-total mass that was because of a more intensive reduction in fat mass than in lean mass implying that dapagliflozin causes improvement of skeletal muscle metabolism (skeletal muscle mass index, SMI). 41 Similarly, in the study conducted by Sasaki et al, the SMI decreased over the course of the treatment, but the degree of the change was small. In our study, the lean-to-body mass between the two arms was maintained at end of therapy.…”
Section: Discussionmentioning
confidence: 81%
“…Another study evaluating the effects of tofogliflozin on body composition revealed that the reduction in BF mass, visceral fat area and skeletal muscle mass was because of the loss of total body water and intracellular and extracellular water, which may have been related with the reduction of body weight 40 . In a study performed to evaluate the effect of dapagliflozin versus glibenclamide on the ratio of lean‐to‐total mass in patients with T2D, it was found that dapagliflozin reduced total body mass but increased the ratio of lean‐to‐total mass that was because of a more intensive reduction in fat mass than in lean mass implying that dapagliflozin causes improvement of skeletal muscle metabolism (skeletal muscle mass index, SMI) 41 . Similarly, in the study conducted by Sasaki et al, the SMI decreased over the course of the treatment, but the degree of the change was small.…”
Section: Discussionmentioning
confidence: 99%